Modifying a behavior intervention plan according to classroom aides acceptability ratings: effects on treatment integrity and challenging behavior. (27th May 2019) - Thomas, Benjamin R.; Lafasakis, Michael
Abstract : This study evaluated the effects of an acceptability questionnaire on classroom aides' treatment integrity during implementation of behavioral intervention plans, using a multiple-probe-baseline across-participants design. Four classroom aides in a special education preschool classroom rarely used procedures recommended to manage the challenging behavior of a four-year-old boy with autism spectrum disorder (ASD) during baseline. After using the questionnaire results to create a functionally equivalent behavior intervention plan that was comprised of components the aides rated as more acceptable, three of the four aides greatly improved their use of the procedures and an ancillary reduction in the child's challenging behavior was observed. Overall, results suggest that including staff acceptance measures during the intervention selection process may bolster subsequent intervention integrity.